Integration of two-phase solid fluid equations in a catchment model for flashfloods, debris flows and shallow slope failures. (July 2018) - Bout, B.; Lombardo, L.; van Westen, C.J.; Jetten, V.G.
Abstract: An integrated, modeling method for shallow landslides, debris flows and catchment hydrology is developed and presented in this paper. Existing two-phase debris flow equations and an adaptation on the infinite slope method are coupled with a full hydrological catchment model. We test the approach on the 4 km 2 Scaletta catchment, North-Eastern Sicily, where the 1-10-2009 convective storm caused debris flooding after 395 shallow landslides. Validation is done based on the landslide inventory and photographic evidence from the days after the event. Results show that the model can recreate the impact of both shallow landslides, debris flow runout, and debris floods with acceptable accuracy (91 percent inventory overlap with a 0.22 Cohens Kappa). General patterns in slope failure and runout are well-predicted, leading to a fully physically based prediction of rainfall induced debris flood behavior in the downstream areas, such as the creation of a debris fan at the coastal outlet. Highlights: We develop a new open source multi-hazard model. Our model simulates catchment hydrology, landslides, debris flows and flash flooding. We apply a novel method for fast estimations of landslide failure volumes. By including hydrology and debris flow runout, we simulate multi-hazard behavior. We apply the model to a study case and found high accuracy in hazard behavior.